Old Calendarism in Romania : People, Facts, Stances : (1924-2022) - MUREȘAN, Radu Petre (Presa Universitară Clujeană, 2023)
My interest in the study of Old Calendarist movement was stirred by an unexpected and painful event in the recent history of the Romanian Orthodox Church: in 2010 priest Nichita Pașcan, the confessor of Brâncoveni Monastery – a convent in the region of Oltenia, together with 29 of its 65 dwellers (nuns), left the convent and joined an Old-Calendarist group in Greece. This prompted me to investigate the past in order to understand the phenomenon itself, since the emergence of this movement in 1924, its evolution throughout various historical periods, and its impact on today’s society. My interest was also stirred by the surprising fact that Fr. Nichita Pașcan and the group of nuns who followed him did not join the Old Calendar Church of Romania, or any other Old-Calendarist group operating on the territory of Romania, but preferred to become affiliated to an Old-Calendarist group in Greece. Hopefully this study published in English will be highly useful to researchers into the history and religious life in the South-East of Europe, especially those interested in the specific character of religious life of Romania during the modern and contemporary period.